Metodologia Ativa: revisão de literatura no contexto da pandemia da COVID-19 - Chagas, Euana das (2022)
The present research deals with active methodology as a methodological option in the teaching and learning processes, focusing on its use in the context of the Covid-19 pandemic for the continuity of classes remotely. The general objective of this study is to carry out a literature review on active methodologies in the field of education. As a result, it was evident that active methodologies were a methodological option used during the Covid-19 pandemic and presented satisfactory results for student learning. The active methods used most frequently by teachers were the flipped classroom and problem-based learning whose objectives were to develop autonomy, interaction, protagonism, as well as creativity and critical thinking. Although the literature on active methodologies demonstrates a diversity of pedagogical theories that support them (DEWEY, FREIRE, VYGOSTSKY, AUSUBEL, ROGERS), we can state that, in all of them, there is an emphasis on the student as the center of the teaching and learning processes